2011
DOI: 10.4314/ajfand.v11i1.65885
|View full text |Cite
|
Sign up to set email alerts
|

Pure water syndrome: Bacteriological quality of Sachet- packed drinking water sold in Nigeria

Abstract: Water is one of the indispensable resources for the continued existence of all living things including man. Government has failed to adequately provide safe, pipe-borne water for the increasing population in Nigeria and this has encouraged the sale of drinking water by private enterprises that have little knowledge about good manufacturing practices. This study investigated the bacteriological quality of commercial sachet-packed drinking water at point-of-sale in southwestern Nigeria with emphasis on pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 14 publications
2
34
0
Order By: Relevance
“…None of the brands examined in this study displayed such required information as batch number, manufacturing date, best before date and nutritional information even though all of the brands provided the producer's name and address including the NAFDAC number. Similar observations have been reported in various parts of Nigeria (Dada, 2009;Edema et al, 2011). The zero compliance to labelling requirements reported in different parts of Nigeria underscores enforcement issues with government regulations when compared to Tanzania showing a 54% compliance rate in a similar study (Kassenga, 2007).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…None of the brands examined in this study displayed such required information as batch number, manufacturing date, best before date and nutritional information even though all of the brands provided the producer's name and address including the NAFDAC number. Similar observations have been reported in various parts of Nigeria (Dada, 2009;Edema et al, 2011). The zero compliance to labelling requirements reported in different parts of Nigeria underscores enforcement issues with government regulations when compared to Tanzania showing a 54% compliance rate in a similar study (Kassenga, 2007).…”
Section: Discussionsupporting
confidence: 74%
“…Research has shown that even though regarded as treated, when sachet water samples were examined for the presence of coliforms; 20-90% incidence of pathogenic bacteria have been reported in some cases (Dada, 2009;Edema et al, 2011). This kind of reports is indicative of non-compliance of manufacturers to NAFDAC and other governmental agencies' guidelines aimed at maintaining the WHO standards for the quality of drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, quite a lot of these brands of sachet-water which the masses perceive as safe for drinking are unsafe. Several surveys and studies have proven that most brands of sachet-water are unwholesome and therefore unfit for drinking, in line with WHO guidelines for drinking water [8,9,10,11,12,5]. While several studies have been carried out by various researchers in Nigeria on the physicochemical and bacteriological quality of sachet-water brands sold in Nigeria-with their findings showing that most of the brands are unwholesome-yet, there seems to be paucity of data in literature on the factors that are responsible for the overwhelmingly reported unwholesomeness of the ubiquitous sachet-water.…”
Section: Introductionmentioning
confidence: 86%
“…Therefore a total of 83 samples were collected instead of the proposed 86. The Sachet water samples were purchased from producers (Ajayi and Adesida, 2009;Ezeugwunne et al, 2009 andOyedeji et al, 2010) and transported to laboratory in insulated containers with ice packs within 8 -24 hour (Okioga, 2007 andEdema et al, 2011). Meanwhile the samples were coded and labeled for easy identification.…”
Section: Materials and Methods Sampling Proceduresmentioning
confidence: 99%